Answer :

Put x = tanθ


θ = tan–1(x)


tan–1{tanθ +}


= tan–1{tanθ +}


= tan–1{tanθ +secθ }


= tan–1


= tan–1


Sinθ = ,cosθ =


= tan–1


= tan–1


= tan–1


Dividing by we get,


= tan–1


= tan–1


= tan–1


tan(x+y) =


= tan–1


=


From 1 we get


= .


Therefore, the simplification of given equation is .


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers